2012
DOI: 10.1371/journal.pone.0035877
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic miR155 Deficiency Enhances Atherosclerosis and Decreases Plaque Stability in Hyperlipidemic Mice

Abstract: microRNA-155 (miR155) is a central regulator of immune responses that is induced by inflammatory mediators. Although miR155 is considered to be a pro-inflammatory microRNA, in vitro reports show anti-inflammatory effects in lipid-loaded cells. In this study we examined the role of miR155 in atherosclerosis in vivo using bone marrow transplantation from miR155 deficient or wildtype mice to hyperlipidemic mice. Hematopoietic deficiency of miR155 enhanced atherosclerotic plaque development and decreased plaque st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
104
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(107 citation statements)
references
References 23 publications
0
104
2
1
Order By: Relevance
“…Impairment of BMP9 signaling is not restricted to genetic disorders. miR-155 is dysregulated in many pathological states, including vascular diseases (33,34). Our studies show that expression of miR-155 promotes podosome rosette formation in BAE cells.…”
Section: Discussionmentioning
confidence: 57%
“…Impairment of BMP9 signaling is not restricted to genetic disorders. miR-155 is dysregulated in many pathological states, including vascular diseases (33,34). Our studies show that expression of miR-155 promotes podosome rosette formation in BAE cells.…”
Section: Discussionmentioning
confidence: 57%
“…These findings are in good correspondence with a recent publication of Du et al, 35 which showed a reduced Ly6C hi monocyte subset in the spleen of global miR-155-deficient mice on an APOE -/-background. However, Donners et al 36 recently found a different result with significantly less Ly6C hi monocytes in the blood lymphocyte profile of mice with an exclusive deficiency of miR-155 in the hematopoietic system. A possible explanation for this discrepancy is that Donners et al 36 obtained their results in a model of chronic hyperlipidemia and exclusive hematopoietic miR-155 deficiency, whereas our model of femoral artery ligation represents an acute inflammatory stimulus in globally miR-155-deficient animals.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, research from our laboratory suggests that miR-155 plays a protective role in the development and progression of AS (19). In a murine model of hyperlipidemia, miR-155 was found to act as an anti-inflammatory and protective factor against AS (20).…”
Section: Introductionmentioning
confidence: 89%